Thermal and economic comparisons of solar heating systems with seasonal storage used in building heating - Ucar, Aynur; Inalli, Mustafa (Pergamon-Elsevier Science Ltd, 2008)
In this study, the thermal performances and economic savings of the three types of central solar heating system with seasonal storage are compared. Three types of seasonal storage were simulated: storage tank without insulation on ground, storage tank with insulation on ground, and underground storage tank without insulation. The long-term temperatures of water in the storage tank are calculated by finite element code ANSyS(TM). The simulation results showed that the higher solar fraction and savings are obtained for system with storage buried into ground. Furthermore, the solar fraction of the storage tank system with insulation is significantly higher than that of without insulation storage system. Also, the solar fraction and savings of system with the evacuated tube collector are higher compared to other black paint flat plate collector. (c) 2008 Elsevier Ltd. All rights reserved.
Keywords: seasonal storage; building heating; solar energy